The comparison of minocycline oral-rinse and gel on pocket depth - Eka Fitria Augustina (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Infection disease is still considered as a prominent disease in many developing countries, like Indonesia. The most oral infection disease is periodontitis. Despite scaling and root planning as the main therapy, minocycline as adjunct therapy has already been used for periodontitis. There are a lot of media used, such as oral rinse and gel. Many researches even have also shown that the use of minocycline as adjunct therapy can decrease inflammation in periodontitis. Like tetracycline, minocycline as an anti inflammatory and anticollagenase is also considered to be very effective for the treatment of periodontitis. Media of minocycline that are available are gel, fiber, and oral rinse, as the newest one. Purpose: The purpose of this research is to examine the comparison of 0.2% oral rinse minocycline and 2% minocycline gel to reduce the pocket depth. Method: The samples were divided into two groups, the first group using oral rinse and the second one using gel after scaling. Result: There was no statistically significant difference between the group with minocycline gel and oral rinse. Conclusion: The application of 2% minocycline gel or 0.2% minocycline mouth wash after scaling and root planning has the same effect in reducing pocket depth.Latar belakang: Penyakit infeksi masih merupakan kasus yang menonjol di banyak negara berkembang, seperti Indonesia. Infeksi rongga mulut yang banyak terjadi adalah periodontitis. Selain terapi utama yaitu skeling dan root planning, menggunakan minosiklin sebagai terapi tambahan telah banyak digunakan, seperti obat kumur dan gel. Banyak penelitian menunjukkan bahwa penggunaan minosiklin sebagai terapi tambahan dapat menurunkan keradangan pada pasien periodontitis. Seperti tetrasiklin, minosiklin sebagai anti keradangan dan anti kolagenase, sangat efektif sebagai perawatan periodontitis. Media minosiklin yang banyak digunakan di antaranya yaitu gel, fiber, dan obat kumur yang terbaru. Tujuan: Tujuan penelitian adalah mengetahui perbandingan antara penggunaan 0,2% obat kumur minosiklin dan 2% minosiklin gel untuk mengurangi kedalaman poketperiodontal. Metode: Sampel dibagi menjadi dua grup, grup pertama menggunakan obat kumur, dan kelompok kedua menggunakan gel, setelah terapi skeling. Hasil: Tidak ada perbedaan yang signifikan antara kelompok minosiklin obat kumur dan gel. Kesimpulan: Minosiklin gel dan obat kumur sama-sama efektif dalam mengurangi kedalaman poket.